The response of Johann Wolfgang von Goethe to the French Revolution - Mortimore, AG (2017)
This thesis seeks to explain the reasons behind Johann Wolfgang von Goethe’s critical response to the French Revolution, and to identify his broader political views. It casts Goethe as a reform-minded conservative, who strove to advance civilisation and law-abiding liberty, and deplored tyranny, whether of the few or of the many. He deemed the Revolution politically and socially destructive, as it countered Enlightenment values of reason, tolerance, independent thought, and self-cultivation. While acknowledging the faults of the traditional ruling elite of the monarchy and aristocracy, Goethe also recognised the inherently flawed nature of human beings. This led him to support modest changes to redress specific grievances, rather than to overturn an entire political system in the utopian hope of realising a vice-ridden ‘brotherhood of Man’. The fictional works indicate an author who favoured clearly definable freedoms over an abstract ‘universal’ freedom, who believed that Bürger should develop their intellect and find an occupation best suited to their personal attributes, and that the most temperate and politically astute among them should influence government by co-operating with aristocrats. Goethe also portrays the fall of the ancien régime as largely self-inflicted, presenting many selfish and gullible courtiers, and incompetent kings. He appears to lament its demise, however, and not wish for a repeat in Germany, as the insurgent Bürger-dominated and/or republican regimes seem even more reckless. The advocates of 'liberté, égalité, fraternité' generally come across as perilously naïve or fraudulent, often using altruistic rhetoric to conceal egocentric and vindictive aims. The best cure for a flagging regime is (sometimes considerable) reform, not revolution. Political power should be treated with humility and self-restraint, and the relationship between rulers and subjects should be as intimate as possible. Above all, no part of the social hierarchy should suffer oppression from another, and people should be free to express various opinions, and criticise their government. For Goethe, the Revolution thwarted such principles.